The effect of corporate social responsibility disclosure on the company’s financial performance with environmental uncertainty as a moderating variable - Ni Komang Apriliani Selumbung; I Putu Sugiartha Sanjaya (Journal of Contemporary Accounting, 2022)
This study aims to provide empirical evidence regarding the effect of Corporate Social Responsibility (CSR) disclosure on financial performance. This study also examines the effect of Environmental Uncertainty (EU) as a moderating variable on the relationship between CSR disclosure and the financial performance of companies listed on the Indonesian Stock Exchange (IDX) in 2019-2020. The study’s secondary data is from annual reports, sustainability reports, and financial information. This study measures CSR disclosure by the Global Reporting Initiative (GRI) G4 standard, return measures financial performance on Equity (ROE), and the EU is measured using a dummy variable. The observations (firm-years) in this study were 673. This study tests the hypothesis by multiple linear regression analyses. This study provides two results. First, CSR disclosure has a positive effect on financial performance. Second, the EU as a moderating variable does not affect the relationship between CSR disclosure and financial performance.